2018
DOI: 10.1371/journal.pone.0195454
|View full text |Cite
|
Sign up to set email alerts
|

CtGEM typing: Discrimination of Chlamydia trachomatis ocular and urogenital strains and major evolutionary lineages by high resolution melting analysis of two amplified DNA fragments

Abstract: Chlamydia trachomatis infects the urogenital tract (UGT) and eyes. Anatomical tropism is correlated with variation in the major outer membrane protein encoded by ompA. Strains possessing the ocular ompA variants A, B, Ba and C are typically found within the phylogenetically coherent “classical ocular lineage”. However, variants B, Ba and C have also been found within three distinct strains in Australia, all associated with ocular disease in children and outside the classical ocular lineage. CtGEM genotyping is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Instead, the unique and genetically distinct strains clustered within lineages that were previously occupied exclusively by UGT isolates (namely genotypes D-K) [39]. Additionally, both ompA genotyping [40] and novel Ct molecular genotyping (CtGEM; developed as a method for high throughput surveillance of strains and the major phylogenetic lineages [41]) of UGT samples obtained from remote indigenous communities also confirmed that Australian ocular strains are distinct from global and Australian UGT strains [40](). Such clustering indicates the polyphyletic evolution of Australian isolates and certainly raises questions around the origins of Ct strains in Australia [39,42], which is an area of continued research.…”
Section: The Curious Molecular Epidemiology Of Ocular and Sexually Trmentioning
confidence: 75%
See 1 more Smart Citation
“…Instead, the unique and genetically distinct strains clustered within lineages that were previously occupied exclusively by UGT isolates (namely genotypes D-K) [39]. Additionally, both ompA genotyping [40] and novel Ct molecular genotyping (CtGEM; developed as a method for high throughput surveillance of strains and the major phylogenetic lineages [41]) of UGT samples obtained from remote indigenous communities also confirmed that Australian ocular strains are distinct from global and Australian UGT strains [40](). Such clustering indicates the polyphyletic evolution of Australian isolates and certainly raises questions around the origins of Ct strains in Australia [39,42], which is an area of continued research.…”
Section: The Curious Molecular Epidemiology Of Ocular and Sexually Trmentioning
confidence: 75%
“…In the same study, seven new STs not described anywhere else in the world were also characterised, five identified within MSM and two within heterosexuals, indicating that the epidemiology might be more complex than previously thought [23]. Molecular Ct studies can certainly be improved in Australia as they can be utilized as a valuable epidemiological tool to track new and/or persistent infections or determine treatment failure, particularly as there is growing concern about the latter [23,41,46].…”
Section: The Curious Molecular Epidemiology Of Ocular and Sexually Trmentioning
confidence: 94%
“…In the last decades other more discriminating typing techniques were also developed, leading to even more CT genotypes, which could be clustered in specific lineages [4,5]. Ocular ompA types are A, B, Ba and C and are still found only in non-Western countries but sometimes also occur in urogenital infections [4,[6][7][8][9][10]. The urogenital genovars B and D to K, infect cervical and vaginal sites in women and anal sites in men and can all also be detected in urine samples.…”
Section: Introductionmentioning
confidence: 99%
“…The urogenital genovars B and D to K, infect cervical and vaginal sites in women and anal sites in men and can all also be detected in urine samples. So genovars B and Ba may be found both at ocular and urogenital locations [6,9] All of the ocular and urogenital genovars are non-invasive types, in contrast to the ompA type L, which is associated with invasive infection leading to Lymphogranuloma venereum (LGV) disease, with swollen lymph nodes and anal ulcers. HIV seropositivity is a strong risk factor for LGV [11] and these LGV infections are mostly found in men who have sex with men (MSM) but in rare cases also in women [6].…”
Section: Introductionmentioning
confidence: 99%
“…A range of studies have reported that HRM analysis of PCR amplicons is a powerful method for detecting sequence variations at any position. Compared to other mutation detection methods, this one has the advantages of sensitivity, ability to detect high levels of heterozygosity and convenient and rapid operation [7][8][9]. For example, Han et al have developed an HRM analysis system for screening and genotyping singlenucleotide polymorphism (SNP) markers in diploid and tetraploid Medicago sativa L. [10].…”
Section: Introductionmentioning
confidence: 99%